Environmental Tools’ International Typology and Research of its Application in Lithuanian Enterprises - Ruževičius, Juozas (Ekonomika, 2003)
During integration into the European Union the enterprises of Lithuania will have to follow internationally accepted standards and the environmental ones as well. Environmental management systems are one of mostly used voluntary environmental means. Only 48 Lithuanian enterprises (0,1 percent of all enterprises) have already implemented these systems. In order to facilitate this process an investigation of motivation, utility and difficulties of environmental management system implementation was performed. Lithuanian enterprises that have environmental management systems certificated according to ISO 14001 standards requirements were analyzed. The analysis shows that the reduction of environmental hazards and costs, increase of competitive ability, the requirements of business partners and efforts to improve their image are the main motives of implementing environmental management systems. Lack of knowledge, the absence of an unanimous record methodology of the system implementation and maintenance costs, lack of governmental sup- port and the shortage of financial and technical resources hinder a faster implementation of environmental management systems. It is recommended to Lithuanian organizations to create integrated environmental and quality management system (ISO 14001 and ISO 9001). Lithuanian government supports financially the implementation of this type of systems. It is proposed to government to support the eco-labelling of Lithuanian products too, because more than 20% of examined enterprises are planning to implement environmental certification of their products. It is recommended to create National programme of consumer education. It is advisable to incorporate a provision into Public purchases law, which lets to keep enterprise’s environmental and quality management systems and eco-label as a competitive advantage.